Penerapan Metode Multi Attribute Utility Theory (MAUT) Dalam Promosi Kenaikan Jabatan Dengan Pembobotan ROC - Khamsah Anugrah Parma Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study applies the Multi Attribute Utility Theory (MAUT) Method with the Rank Order Centroid (ROC) weighting approach in the promotion process at PT Gruti Lestari Pratama Mandailing Natal. This method provides an effective framework to overcome subjectivity in selecting the most suitable employees for promotion, based on criteria such as Length of Service, Performance, Loyalty, and Attendance. The steps of the implementation scenario include inputting criteria data, weighting using ROC, inputting sub-criteria data, alternative data, and assessment. The decision-making process is carried out through the MAUT Method, which integrates criteria preferences and assessments. The results of this study obtained that the best alternative with a final utility value of 1.002 was